Pengaruh Kualitas Produk, WOM, Komunitas Pelanggan Terhadap Keputusan Pembelian Keripik Sukun Sedap Malam di MasaPandemi di Dusun Setimbo Desa Jati Banteng Kecamatan Jati Banteng Kabupaten Situbondo - Sutrisno, Mashluhah; Maheni Ika Sari; Tatit Diansari Reskiputri (Universitas Muhammadiyah Metro, 2024)
Purchasing decision is a concept of purchasing behavior where a consumer decides to do something or do something. One of the factors is the quality of the product, word of mouth and also the customer community. The method used in this research is descriptive quantitative. The population and research sample are consumers who have bought sukun sedap malam chips products in Setimbo Hamlet, Jati Banteng Village, Jati Banteng District, Situbondo Regency (heterogeneous population), at least 97 people. The data collection technique used a questionnaire. The analytical tool used is to use multiple linear analysis. The results showed that product quality and customer community had an effect on purchasing decisions for night savory breadfruit chips, while WOM had no significant effect on purchasing decisions for night savory breadfruit chips.